Finite element and preclinical analysis of tissue response to negative pressure wound therapy with a felted foam containing 10 mm through holes - McNulty, Amy K.; Wilkes, Robert P.; Marchand, Brenda; Ingram, Shannon; Mann, Samantha; Sieracki, James (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionNot all wound patients are candidates for surgical debridement. A felted, reticulated open cell foam with an array of 10 mm holes (VFCC) for use with instillation therapy has been used to eliminate non-viable tissue from patient wound beds. The mechanisms for this have not been fully elucidated. The current study elaborates the biomechanical stresses, strains and work imparted to tissue with VFCC versus commonly used reticulated open cell foam (ROCF) dressings.MethodsFinite element analysis (FEA) measured strain and deformation occurring at the tissue interface with VFCC or ROCF. FEA results were compared to those in a preclinical, porcine sloughy wound model.ResultsThe peak maximum principal strain imparted to tissue at –125 mmHg with VFCC was 27.8% versus 0.9% with ROCF. The frictional work around the holes in the VFCC was 0.179 mJ while negligible with ROCF.DiscussionThe FEA model predicted high strains at the sides of the macrodomes of tissue pulled into the through holes and was consistent with slough removal in the preclinical study. Frictional work around the 10mmholes in the VFCC may pin the tissue leading to higher strain energy densities as tissue is pulled into the holes allowing for fracturing and removal of devitalized tissue.